Migrant Health: a value for Public Health (Italian Journal of Public Health, 2012)
The health matters associated with migration are crucial public health challenges faced by both governments and societies. According to United Nations estimates, 120 million of the approximately 175 million migrants worldwide are migrant workers with their families. Legal and illegal workers have a different status and, therefore, varying levels of access to social and health services. The collective health needs and implications of this sizeable population are considerable, and different health determinants and levels of vulnerability could impact on their health. The main public health goal is to avoid disparities in health status and access to health services between migrants and the host population. The second, closely associated principle, is to ensure migrants’ health rights, as stated during the 4th Conference on Migrant and Ethnic Minority Health in Europe which took place from 21st to 23rd June 2012 in Milan, where Migrants and ethnic minorities were confirmed as a benefit to the society.